2021
DOI: 10.1021/acs.nanolett.1c03018
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Thermal Conductivity of Crystalline Layered SnSe2

Abstract: The degree of thermal anisotropy affects critically key device-relevant properties of layered two-dimensional materials. Here, we systematically study the in-plane and cross-plane thermal conductivity of crystalline SnSe2 films of varying thickness (16–190 nm) and uncover a thickness-independent thermal conductivity anisotropy ratio of about ∼8.4. Experimental data obtained using Raman thermometry and frequency domain thermoreflectance showed that the in-plane and cross-plane thermal conductivities monotonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
2
25
1
Order By: Relevance
“…It is found that the P2 mode is more sensitive to temperature, which may be related to the vdW force between layers. These χ values are greater than those of MoS 2 , graphene and SnSe 2 , indicating that R-ZIS flakes possess relatively strong interlayer interactions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is found that the P2 mode is more sensitive to temperature, which may be related to the vdW force between layers. These χ values are greater than those of MoS 2 , graphene and SnSe 2 , indicating that R-ZIS flakes possess relatively strong interlayer interactions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For the thermal measurements, we used a custom-built frequencydomain thermo-reflectance (FDTR) setup, a well-established optical pump-probe technique, capable of measuring heat transport in thin films and across interfaces [31][32][33][34][35][36] . A schematic representation of the experimental setup is shown in Fig.…”
Section: Thermal Conductivity and Interfacial Heat Transport Measurem...mentioning
confidence: 99%
“…We used a lock-in amplifier (Zurich Instruments HF2LI) to record the amplitude and phase response of the reflected probe beam to the thermal wave, and the phase lag between the pump and probe beam as the observable quantity. More details on the experimental setup can be found elsewhere 35 .…”
Section: Thermal Conductivity and Interfacial Heat Transport Measurem...mentioning
confidence: 99%
“…45 These low-dimensional materials are particularly interesting in nanophononics due to their ability to confine phonons as they approach length scales in which their finite size or thickness begins to have a strong effect on material properties such as the thermal conductivity. 22,46 For example, in the case of nanoparticles, the confinement resulting from the edges of the nanoparticle leads to a break in translational symmetry in the crystal (i.e., absence of periodicity beyond the limits of the particle). This loss of symmetry leads to a shift of the optical Raman modes and an asymmetric broadening of the signal, usually observed as a "shoulder" at lower wavenumber as shown in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Rather, the modification of the thermal conductivity is mainly attributed to diffuse scattering of phonons at boundaries. Although this mechanism has been widely explored and exploited, [22][23][24] recent works propose using phonon coherence to control heat flow. [25][26][27] In this scenario, modification of the phonon dispersion relation by adding additional periodicity to the system by alternating thin layers of dissimilar materials (superlattices), 28 patterning holes in a suspended system, 29,30 or by self-assembling colloidal particles, 31,32 offers a simple strategy to manipulate phonon waves.…”
Section: Introductionmentioning
confidence: 99%